MATH SOLVE

2 months ago

Q:
# How do you write y+1=4/5(x-3) in standard form?

Accepted Solution

A:

Answer:The standard form of the given expression is [tex] - (\frac{4}{5})x + y + (\frac{17}{5}) = 0[/tex]Step-by-step explanation:Here, the given expression is [tex]y + 1 = \frac{4}{5} (x-3)[/tex]Now, the Standard Form of the equation is ax + by + c = 0Solving this, we get: [tex]y + 1 = \frac{4}{5} (x-3) \implies y + 1 = (\frac{4}{5})x - \frac{12}{5}[/tex]⇒[tex]y + 1 - (\frac{4}{5})x + (\frac{12}{5}) = 0[/tex]or, [tex]y - (\frac{4}{5})x + (\frac{12}{5} + 1 )= 0 \implies y - (\frac{4}{5})x + (\frac{12+ 5}{5}) = 0[/tex]⇒[tex]y - (\frac{4}{5})x + (\frac{17}{5}) = 0[/tex]Hence, the standard form of the given expression is [tex] - (\frac{4}{5})x + y + (\frac{17}{5}) = 0[/tex]